1987
DOI: 10.1159/000212895
|View full text |Cite
|
Sign up to set email alerts
|

Hyposomatomedinemia in the Men of a Veterans Administration Nursing Home: Prevalence and Correlates

Abstract: A previous study found hyposomatomedinemia to be common in the men of this VA Nursing Home. To gain information on the prevalence and correlates of this endocrine characteristic, we have measured plasma somatomedin C (SmC) in 69 Nursing Home men 55–95 years old (group I), and in 37 independent men 56–87 years old attending our geriatric medicine outpatient clinic (group II). In groups I and II, a clinical data base was compiled comprising: blood chemistries, measures of body composition – nutritional state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Thus, the data do not exclude the possibility that immobility (as contrasted with a sedentary life style) would further lower the IGF‐I level in aging people. Militating against this postulate, however, is a previous finding that within a nursing home population, the serum IGF‐I concentration did not correlate significantly with the degree of physical dependency 25 . (3) The GH response to exercise by young people is known to be proportional to the duration and intensity of the exercise 26–28 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the data do not exclude the possibility that immobility (as contrasted with a sedentary life style) would further lower the IGF‐I level in aging people. Militating against this postulate, however, is a previous finding that within a nursing home population, the serum IGF‐I concentration did not correlate significantly with the degree of physical dependency 25 . (3) The GH response to exercise by young people is known to be proportional to the duration and intensity of the exercise 26–28 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors have previously reported that plasma SmC is significantly lower in nursing home men than in their age‐matched healthy counterparts 43 , 44 . Because the hyposomatomedinemia of these chronically institutionalized individuals was not significantly correlated with their functional level, the writers previously concluded that physical inactivity was not the main cause for their low SmC values 44 . The present finding that the totally immobile subgroup of the male nursing home population did not differ significantly in plasma SmC level from healthy age‐matched men is consistent with the earlier conclusion that physical inactivity per se does not cause hyposomatomedinemia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have previously reported that plasma SmC is significantly lower in nursing home men than in their age‐matched healthy counterparts 43 , 44 . Because the hyposomatomedinemia of these chronically institutionalized individuals was not significantly correlated with their functional level, the writers previously concluded that physical inactivity was not the main cause for their low SmC values 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, circulating levels of bioavailable testosterone were unrelated to bone mineral density of the proximal femur and the total body in 38 healthy men between 25 and 59 years of age ( Johansson et al, 1994). It remains for future studies to determine if (or to what extent) the lower limit of the normal range for serum testosterone is associated with reduced bone formation and bone fragility in aging men (Rudman et al, 1987).…”
Section: Age-related Factors In the Pathogenesis Of Hip Fracture In Ementioning
confidence: 94%